Handbook of spatial cognition - Waller, David A.; Nadel, Lynn (American Psychological Association, 2013)
"Spatial cognition is a branch of cognitive psychology that studies how people acquire and use knowledge about their environment to determine where they are, how to obtain resources, and how to find their way home. Researchers from a wide range of disciplines, including neuroscience, cognition, and sociology, have discovered a great deal about how humans and other animals sense, interpret, behave in, and communicate about space. This book addresses some of the most important dimensions of spatial cognition, such as neuroscience, perception, memory, and language. It provides a broad yet detailed overview that is useful not only to academics, practitioners, and advanced students of psychology, but also to city planners, architects, software designers, sociologists, and anyone else who seeks to understand how we perceive, interpret, and interact with the world around us"--Publicity materials. (PsycINFO Database Record (c) 2012 APA, all rights reserved).